2015
DOI: 10.1016/j.nepig.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepigenetic regulation of pathogenic memories

Abstract: Our unique collection of memories determines our individuality and shapes our future interactions with the world. Remarkable advances into the neurobiological basis of memory have identified key epigenetic mechanisms that support the stability of memory. Various forms of epigenetic regulation at the levels of DNA methylation, histone modification, and non-coding RNAs (ncRNAs) can modulate transcriptional and translational events required for memory processes. By changing the cellular profile in the brain’s emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 103 publications
1
10
0
Order By: Relevance
“…In their opinion further research on memory reconsilidation could help to ameliorate maladaptive memories and potentiate adaptive behaviors in psychopathology ( Alberini and LeDoux, 2013 ). Sillivan et al (2015) explore the possibilities of latest research on epigenetic modification. They advocate for a recognition of the contribution of epigenetic mechanisms to how pathological memories associated with addiction and PTSD are stored, expressed, and subsequently modified, possibly leading to novel therapeutic targets ( Sillivan et al, 2015 ).…”
Section: Pathogenic Memoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their opinion further research on memory reconsilidation could help to ameliorate maladaptive memories and potentiate adaptive behaviors in psychopathology ( Alberini and LeDoux, 2013 ). Sillivan et al (2015) explore the possibilities of latest research on epigenetic modification. They advocate for a recognition of the contribution of epigenetic mechanisms to how pathological memories associated with addiction and PTSD are stored, expressed, and subsequently modified, possibly leading to novel therapeutic targets ( Sillivan et al, 2015 ).…”
Section: Pathogenic Memoriesmentioning
confidence: 99%
“… Sillivan et al (2015) explore the possibilities of latest research on epigenetic modification. They advocate for a recognition of the contribution of epigenetic mechanisms to how pathological memories associated with addiction and PTSD are stored, expressed, and subsequently modified, possibly leading to novel therapeutic targets ( Sillivan et al, 2015 ).…”
Section: Pathogenic Memoriesmentioning
confidence: 99%
“…Various forms of epigenetic regulation at the levels of DNA methylation, histone modification, and non-coding RNAs (ncRNAs) can modulate transcriptional and translational events required for memory processes [ 10 ]. About 60% of genes harbor CpG- and GC-rich DNA sequences in their 5′ regulatory region, which are termed CpG island promoters [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active genes are associated with an open and unmethylated CpG island promoter and hypermethylated CpG islands are correlated with epigenetically silenced genes [ 12 , 13 ]. By changing the cellular profile in the brain's emotional, reward, and memory circuits, these epigenetic modifications have also been linked to perseverant, pathogenic memories typical for post-traumatic stress disorder (PTSD), major depressive disorder (MDD) and BPD [ 10 , 14 ]. Since environmental stimuli can influence epigenetic modifications, like DNA methylation, these aberrant marks could be associated with the development of anxiety [ 15 ], suicidality [ 16 ], and vulnerability for stress [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that not only genetic factors but also environmental factors play a pivotal role in the etiology and/or progression of age-related cognitive and memory decline in neurodegenerative disorders. It has been shown that environmental factors such as repeated exposure to toxins, stress, lifestyle, quality of diet and nutrients that we are exposed to in our life could alter gene expression and function by epigenetic mechanisms resulting in many diseases or neurological disorders (1,2). Many comprehensive studies have shown that nutrition has a great impact on our physical and mental health.…”
Section: Introductionmentioning
confidence: 99%